Pengaruh Model Pembelajaran Kooperatif Tipe STAD (Student Team Achievement Division) Terhadap Hasil Belajar Pak Siswa Kelas VII SMP Negeri 2 Paranginan Tahun Pembelajaran 2022/2023 - Ezra S.G Siburian; Sudirman Lase; Andar Gunawan Pasaribu; Lince Sihombing; Damayanti Nababan (Universitas Katolik Widya Karya Malang, 2023)
The aim of this research is to determine the positive and significant influence of the STAD (Student Team Achievement Division) Cooperative Learning Model on the PAK Learning Outcomes of Class VII Students of SMP Negeri 2 Paranginan for the 2022/2023 Academic Year. The method used in this research is a quantitative inferential statistical research method. The population is all class VII students of SMP Negeri 2 Paranginan for the 2022/2023 academic year, totaling 65 people. Data collected using a positive closed questionnaire totaled 21 items for variable 2023: 1) Test analysis requirements: a) positive relationship test obtained rxy = 0.480 > rtable(a=0.05,n=65) = 0.244. b) Testing a significant relationship obtained a value of tcount= 4.343 > ttable(a=0.05, dk=n-2=63)= 2.000. 2) Influence test: a) Regression equation test, obtained the regression equation Y ̂=